IDENTIFIKASI HASIL HUTAN BUKAN KAYU GENUS Amorphophallus di DESA SANTONG, KECAMATAN KAYANGAN KABUPATEN LOMBOK UTARA - Irwan Mahakam Lesmono Aji; Endah Wahyuningsih; Patoni Patoni (Jurnal Belantara, 2018)
Lombok Island has an area of 163,342.99 ha comprise of Production Forest, Conservation Forest and Protected Forest. Protected forests in Lombok have non-timber forest products potential, and one of which is from genus Amorphophallus that has economic value. These plants grow naturally in the forest and have a variety of names as well as uses for these plants. The absence of clear scientific names and descriptions of these plants urge the need to study the genus Amorphophallus growing in the island of Lombok, specifically in the Santong Protection Forest area. The purpose of this study is to identify the various species of the genus Amorphophallus and give them a complete scientific description. This research was conducted for five months between June to October of 2013. The methods used in this research are the exploration method and the descriptive method. The results concluded that there are two types of the genus Amorphophallus in the Santong Protected Forest Area, which are 1. Amorphophallus muelleri Blume, 2.Amorphophallus campanulatus Blume.